Comparison of Self and Students\' Evaluation of Faculty Members in School of Health of Hormozgan University of Medical Sciences - Teymour Aghamolaei; Sedighe Abedini (مجله ایرانی آموزش در علوم پزشکی, 2008)
Introduction: Comparing the results of students' evaluation and faculty members' self-evaluation can reveal the strengths and weaknesses of faculty members in teaching. The aim of this study was to compare students' evaluation of teaching and faculty members' self-evaluation in School of Health in Bandar Abbas. Methods: The population under study in this cross-sectional survey was faculty members and students of School of Health in Bandar Abbas University of Medical Sciences. Twenty faculty members selected through census sampling method evaluated themselves. In addition to self-evaluation, each faculty member was evaluated by 20 students who were selected randomly. The data gathering tool was a questionnaire consisted of 20 questions with 5 point Likert scale. Data was analyzed by SPSS software. Results: The mean of the faculty members' self evaluation scores was 89.7±6.3 and the mean of this evaluation by students was 85.1±6.5 which demonstrated a significant difference. The correlation coefficient between the scores of self-evaluation and evaluation by students was 0.26. The scores of self-evaluation for most faculty members (75 percents), was higher than the scores of evaluation by students. Conclusion: The results of faculty members' self-evaluation are exploitable for improving the quality of teaching. It is recommended that faculty members take students' evaluation of teaching into consideration more seriously.